Present drugs and future perspectives in treating soil-transmitted helminthiasis - Keiser, Jennifer (Frontiers in Tropical Diseases, 2023)
Soil-transmitted helminthiases caused by Ascaris lumbricoides, Trichuris trichiura, and hookworm (Ancylostoma duodenale and Necator americanus) are responsible for the infection of approximately 1.5 billion people worldwide, mostly in tropical and subtropical regions. Preventive chemotherapy is the mainstay of control, which is the regular administration of anthelminthic drugs, mainly albendazole and mebendazole to at-risk populations. As benzimidazoles face a risk of developing drug resistance and have shortcomings in their therapeutic profile, efforts have been made to develop alternative anthelminthics. The aim of this review is to provide a state-of-the-art update on available treatments and ongoing efforts in Research and Development (R&D) for the three main soil-transmitted helminth infections. Recent findings on the use of drug combinations and advanced drug candidates such as oxantel pamoate and emodepside and how these drugs fulfill the target product profile will be reviewed. Lastly, progress in drug discovery will be summarized.